SINTESIS DAN KARAKTERISASI NUKLEOTIDA BERTANDA [α-32P]ATP - Rahman, Wira Yusril; Sarmini, Endang; Herlina, H.; Abidin, A.; Triyanto, T.; Hambali, H.; Nurbaiti, Santi (Jurnal Riset Kimia, 2019)
The utilization of nuclear technology in health sector with molecular techniques is increasingly developed today, especially in Indonesia.  One of which is nucleotide compound marked with [α-32P]ATP, this compound has been used as tracer for deoxyribonucleic acid (DNA)/ ribonucleic acid (RNA) in the study of various physiological and pathological processes. [α-32P]ATP is synthesized through several stages of continuous reaction in one reaction vessel. It begins with synthesis of [γ-32P]ATP through an enzymatic reaction, using H332PO4 and ADP, and enzymes  of lactate dehydrogenase, 3-phosphoglycerate phosphokinase and glyceraldehide 3-phospho  dehydrogenase; followed by phosphorilation of 3’AMP with T4 polinucleotide kinase enzyme to produce 3’-[5’-32P]ATP. The result is hydrolyzed with nuclease P1 enzyme to produce [5’-32P]AMP. The unreacted [γ-32P] is degraded by the addition of hexokinase enzyme and glucose. At the final stage of the reaction, the [5’-32P]AMP is  phosphorilated using phosphoenol-piruvat, piruvat kinase, and myokinase to produce [α-32P]ATP. The test results show that the every stage of reaction is characterized using TLC method, PEI cellulose paper as stationary phase and KH3PO4 0,5 M pH 3,5 as mobile phase. At the end of reaction, the yield of [α-32P]ATP reaches 71,7%, at Rf = 0,2.